Service-learnig and games as a strategy for the transfer of mathematical knowledge - Sánchez-Cruzado, Cristina; Raya-Fernández, Álvaro; Moral-Sánchez, Silvia Natividad; Sánchez-Compaña, María Teresa (Universidad de Alicante, 2022)
4 researcher-professors and 168 students 2nd year of Primary Education Degree at the University of Malaga, subject Didactics of Arithmetic, carried out a Service-Learning experience. The objective was to design and develop games with manipulative materials, which were taken to two Public Primary Education centers. We wanted to show how Service-Learning promoted greater practical training and formation of values in future teachers who will have a key role in society (Rodríguez-Gallego, 2014), and to assess the groups’ opinion. According to Alsina (2011), the game is a symbolic content activity, through which students carry out a process of adaptation to reality and solve problems that they could not do with real content in the real world. Games and the handling of materials promote mathematical skills development. The university students organized themselves into 32 groups of 4 to 6 people. They went to the schools with mathematical games adapted to the different primary levels. They took some traditional materials, such as Cuisenaire rods, vertical abacuses, tables of 100 number and Multibase Arithmetic Blocks. Furthermore, the university students made some of the materials by hand, and some of them were also customized with different themes. In addition, they adapted traditional games such as Monopoly (called "Mathpoly"), Bingo, dominoes, roulette and cards with numerical operations, among many others. These university students showed the pupils from primary schools how to play and played with them.
Universidad de Málaga. Campus de Excelencia Internacional Andalucía Tech
Keywords: Matemáticas - Estudio y enseñanza - Congresos; Enseñanza primaria - Congresos; Service-learning; Mathematic education; Games; Manipulative materials